Transformasi Manajemen Pendidikan Islam pada Era Kecerdasan Buatan (Artificial Intelligence): Tantangan, Peluang, dan Arah Pengembangannya di Indonesia - La Ode Nasir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid advancement of artificial intelligence has significantly transformed the governance and management of educational institutions, including Islamic educational institutions. This development requires Islamic educational institutions to reform their management practices in order to enhance organizational effectiveness while preserving Islamic values as the foundation of educational provision. This study aims to analyze the transformation of Islamic educational management in the era of artificial intelligence, identify its challenges and opportunities, and formulate future development directions in Indonesia. The study employed a qualitative approach using a narrative literature review method. Data were collected from scholarly journal articles, books, conference proceedings, and official documents published within the last five years. The literature was retrieved through Google Scholar, Scopus, Crossref, and DOAJ, and subsequently analyzed using content analysis to generate a comprehensive synthesis of existing knowledge. The findings indicate that the transformation of Islamic educational management extends beyond the digitalization of administrative processes and encompasses changes in leadership, organizational governance, data-informed decision-making, human resource capacity building, and the improvement of educational services. The review also reveals several major challenges, including limited digital literacy, inadequate technological infrastructure, data security concerns, ethical issues, and organizational resistance to change. At the same time, technological advancement offers substantial opportunities to improve administrative efficiency, transparency, accountability, institutional collaboration, and evidence-based decision-making. Therefore, the future development of Islamic educational management in Indonesia should prioritize strengthening human resource capacity, promoting adaptive governance, formulating responsive institutional policies, and integrating technological innovation with Islamic values to establish high-quality, competitive, and sustainable educational institutions.